2007
DOI: 10.2307/30035545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Determination Interventions on the Academic Skills of Students with Learning Disabilities

Abstract: Given the importance of both academic and self-determination skills for students with disabilities, it is important to identify efficient ways to deliver instruction in these essential areas. This literature review synthesizes intervention research that has examined the effects of self-determination interventions on academic skills for students with learning disabilities (LD) and/or attention deficit/hyperactivity disorder (ADHD). Our findings revealed that self-management interventions were most often studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
120
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 55 publications
3
120
1
4
Order By: Relevance
“…The results of this study showed a positive correlation between self-determination instruction delivered by special education teachers and the academic performance of students with disabilities, which is consistent with findings of past research [10,11,13,17,31]. The students who participated in this study were quite diverse, including students with mild to moderate intellectual disabilities, autism, and multiple disabilities and were selected from varied settings, from resource rooms to self-contained classrooms.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The results of this study showed a positive correlation between self-determination instruction delivered by special education teachers and the academic performance of students with disabilities, which is consistent with findings of past research [10,11,13,17,31]. The students who participated in this study were quite diverse, including students with mild to moderate intellectual disabilities, autism, and multiple disabilities and were selected from varied settings, from resource rooms to self-contained classrooms.…”
Section: Discussionsupporting
confidence: 78%
“…International studies have also confirmed that self-determination and academic performance of students with disabilities are closely related. Regardless of the type of disabilities, such as learning disabilities [17,31], intellectual disabilities & autism [10,11], and multiple disabilities [4], students with a higher degree of selfdetermination tend to have better academic performance, whereas the academic performance of students with a lower degree of self-determination is likely to be poorer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the majority of paraprofessionals reported sometimes or often being involved in teaching each skill. Although some skills (e.g., problem-solving skills, choice-making skills) were reported to have been addressed somewhat more often than others (e.g., goal setting and attainment, decision making), paraprofessionals' reports provide further evidence that self-determination instruction is gaining a noticeable place in the education of students with high-incidence disabilities (Eisenman, 2007;Konrad, Fowler, Walker, Test, & Wood, 2007). Unfortunately, we do not know the specific forms that this instruction took (e.g., curricular programs, discrete instruction, encouraging skill use) or the extent to which highly qualified teachers directed and supervised these efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Self-determination skills enable students with disabilities to have improved academic performance (Konrad, Fowler, Walker, Test, & Wood, 2007), and successful postschool education, employment, and community living outcomes (Martorell, Gutierrez-Recacha, Pereda, & Ayuso-Mateos, 2008;Test et al, 2009;Wehmeyer & Schwartz, 1997).…”
mentioning
confidence: 99%